Trends, Frequency, and Nature of Surgeon-Reported Conflicts of Interest in Plastic Surgery. Issue 4 (October 2017) - Lopez, Joseph; Musavi, Leila; Quan, Amy; Calotta, Nicholas; Juan, Ilona; Park, Angela; Tufaro, Anthony P.; May, James W.; Dorafshar, Amir H.
Abstract : Background: The purpose of this study was to identify types and trends in industry sponsorship of plastic surgery research since the establishment of conflict-of-interest reporting policies in plastic surgery. Methods: The authors analyzed the frequency and types of self-reported conflicts of interest in the plastic surgery literature since the adoption of reporting policies in 2007. All original articles that met the authors' inclusion criteria and were published in the following three journals from 2008 to 2013 were included: Annals of Plastic Surgery, Plastic and Reconstructive Surgery, and Journal of Plastic, Reconstructive & Aesthetic Surgery . A multivariate regression analysis was performed to determine what study-specific variables were associated with conflict-of-interest disclosures. Results: A total of 3722 articles were analyzed. The incidence of conflicts of interest increased from 14 percent in 2008 to 24 percent in 2009. However, thereafter, the incidence of conflicts of interest decreased steadily from 21 percent in 2010 to 9 percent in 2013. Furthermore, the authors' analysis revealed that from 2008 to 2013, industry decreased direct research support but steadily increased the rate of consultantships ( p < 0.001). A multivariate regression analysis revealed that, after adjusting for potential confounders, self-reported conflicts of interest have decreased since 2008 ( p = 0.03) and the prevalence of conflicts of interest differs by plastic surgery subspecialty ( p < 0.0001), country of origin ( p < 0.0001), and journal of publication ( p = 0.05). Conclusions: If self-reporting of conflicts of interest is assumed to be accurate, the number of surgeon-reported conflicts of interest in plastic surgery declined overall. Although the absolute number of consultantships did not change, the rate of consultantships rather than direct research support increased over this period.